Multi-hole extrusion process: A review. (2022) - Sahu, Rita Kumari; Das, Ratnakar; Routara, B.C.; Nayak, Bijaya Bijeta; Sahu, Sasmita
Abstract: Extrusion process has played a big role in the metal forming industries for production of many metallic materials of different cross-sections. The die design, lubrication conditions and other parameters are well established with conventional extrusion process. Multi-hole extrusion process uses die with more than one orifice and accordingly more than one product can be obtained during extrusion. The extruded parts obtained from multi-hole extrusion process show different length, mechanical properties as the effect of different process parameters are different. The present review work focuses multi-hole extrusion and its significance to industrial revolution. This review work will provide insights of different methods of understanding the process, effect of different process parameters on extruded product length, product quality and mechanical as well physical properties.